Improving Students' Spatial Thinking Skills Through the Integration of Project-Based Learning with Google My Maps - Bella Zulfia Aisyatul Wahidah; Muh Sholeh; Dewi Liesnoor Setyowati; Edi Kurniawan; Erni Suharini (Universitas Negeri Medan, 2026)
Students' spatial thinking ability is one of the important competencies in geography learning; however, in practice, this ability remains underdeveloped, so learning innovations are needed to improve spatial thinking skills. This study aims to analyze the effectiveness of integrating Project Based Learning with Google My Maps in improving students' spatial thinking ability. This study used a Quasi-Experimental method with a one-group pre-test and post-test design. The population of this study was tenth-grade students of SMA Negeri 1 Parakan, with the sample being class X-6, selected through purposive sampling technique. Data collection in this study was carried out using observation, test, questionnaire, and documentation techniques. The analysis techniques used in this study were the Paired T-Test, N-Gain, Cohen's d, classical completeness analysis of 75%, and student response analysis. The paired t-test results obtained a Sig. (2-tailed) value of 0.001, indicating a significant improvement in students' spatial thinking ability. Classical completeness reached 92%, exceeding the established criterion of 75%. Student response to the learning was classified as positive, with a percentage of 78.4%, while the N-gain calculation of 61.8% falls into the fairly effective category, and Cohen's d of 2.64 falls into the large effect category. Based on these findings, the integration of Project Based Learning with Google My Maps is proven to be fairly effective in improving students' spatial thinking ability in geography learning.